2018
DOI: 10.1080/13811118.2017.1392915
|View full text |Cite
|
Sign up to set email alerts
|

Developing Adaptive Treatment Strategies to Address Suicidal Risk in College Students: A Pilot Sequential, Multiple Assignment, Randomized Trial (SMART)

Abstract: This pilot study investigated the potential to utilize adaptive treatment strategies for treating moderate to severe suicidal risk among college students. This article will describe the unique study design and report on feasibility and acceptability findings. A 2-stage Sequential Multiple Assignment Randomized Trial (SMART) was conducted: In Stage 1, 62 suicidal college students were randomized to either a suicide-focused or a treatment-as-usual condition (4-8 weeks). Those deemed insufficient responders were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
1
15
0
1
Order By: Relevance
“…In addition to implementation outcomes, there were promising outcomes related to STB. The majority of youth resolved, according to CAMS criteria, demonstrating four consecutive weeks of no STB, management of urges, and low self-reported suicide risk, similar to the response rates obtained in adult populations (Pistorello et al, 2018) as well as other well-established interventions for selfinjury (i.e., in the CARES DBT trial 54.2% of youth had no injury at the end of the intervention; McCauley et al, 2018). When the severity of suicidal ideation was used as the primary outcome, a moderate effect size was observed in reduction of suicidal ideation, on par with other brief programs but smaller in impact than the CAMS trial with adults (Ellis et al, 2017;Jobes et al, 2017) and other more comprehensive programs for youth (i. e., DBT;McCauley et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…In addition to implementation outcomes, there were promising outcomes related to STB. The majority of youth resolved, according to CAMS criteria, demonstrating four consecutive weeks of no STB, management of urges, and low self-reported suicide risk, similar to the response rates obtained in adult populations (Pistorello et al, 2018) as well as other well-established interventions for selfinjury (i.e., in the CARES DBT trial 54.2% of youth had no injury at the end of the intervention; McCauley et al, 2018). When the severity of suicidal ideation was used as the primary outcome, a moderate effect size was observed in reduction of suicidal ideation, on par with other brief programs but smaller in impact than the CAMS trial with adults (Ellis et al, 2017;Jobes et al, 2017) and other more comprehensive programs for youth (i. e., DBT;McCauley et al, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Dissociation has been shown to predict poor response to dialectical behavioral therapy (DBT) in female patients with BPD (Kleindienst et al, 2011). As DBT is the most evaluated and recommended psychotherapy for college students with BPD (Meaney-Tavares and Hasking, 2013;Lin et al, 2018;Pistorello et al, 2012Pistorello et al, , 2017Uliaszek et al, 2016), future studies on DBT in college students or application of DBT to college students should consider the frequent association of borderline, schizotypal symptoms and dissociation.…”
Section: Cluster Analysis Based On Borderline and Schizotypal Factorsmentioning
confidence: 99%
“…Based on a search of studies identified in early August 2015 via the www.clinicaltrials.gov website (search terms [“adaptive treatment” or “adaptive intervention” or “adaptive strategy” or “sequential treatment”] crossed with [“children”, “child”, “adolescent” or “youth”], or with the terms [“sequential multiple assignment randomized trial” or “sequential, multiple assignment, randomized trial”]), we wish to note that there is other exciting work on adaptive interventions being done in the areas of adolescent marijuana use (Budney, Stanger, & colleagues, 2014; Kaminer & colleagues, 2012), prevention of oppositional behavior (Dishion et al, 2014), child depression (Eckshtain, 2013), autism (Kasari & colleagues, 2012), college student suicide prevention (Pistorello & colleagues, 2015), child trauma (Salloum, Robst, et al, 2014; Salloum, Scheeringa, Cohen, & Storch, 2014), and child and adolescent obsessive-compulsive disorder (Shavitt & colleagues, 2010). 1 …”
Section: Ongoing and Future Workmentioning
confidence: 99%